Use of mineral residue from lithium processing as fertilizer in the cultivation of castor beans (Ricinus communis L.) - Costa, Aline Aparecida Andrade; Costa, Alexandre Sylvio Vieira da; Costa, Márcia Regina da; Viana, Abraão José Silva (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Research into the characteristics and potential of new sources of fertilizers has expanded, but still deserves study efforts to establish and recommend agronomic methods. This project aimed to use the residue from lithium processing as fertilizer in the production of castor beans ( Ricinus communis L.). The research included the chemical characterization of residues, development of castor bean plants in terms of assessments of fresh and dry weight of roots, stem, leaves, fruits, plant height, diameter and height of the plant, production of fruits and seeds, determination of the content of oil to diameter and height, and foliar analysis after harvest at 180 days. Experiment in a greenhouse at UFVJM in Diamantina, MG, using a randomized block design (DBC), 2x7 factorial scheme, four replications. 1st treatment consisting of with and without application of 10% of the total applied Aluminum Silicate in Calcinator Furnace Fines (0, 0.1, 0.2, 0.4, 0.6, 0.8 and 1.0t/ ha) + 50% conventional fertilizer. 2nd treatment: seven doses of Aluminum Silicate (0, 1, 2, 4, 6, 8 and 10t/ha). In the soil analysis, there was a greater increase in the levels of K, P and effective CTC of Ca and K using the 1st treatment. In the development and production of castor oil, the 1st treatment with dosages 8 and 10 t/ha + 1.0 t/ha + 50% fertilization showed greater development in phytotechnical analyzes and oil content. The 0 t/ha dosage of the 2nd treatment had the lowest development.